INTERROGATING THE FUNDAMENTAL CHALLENGES MILITATING AGAINST THE TEACHING AND LEARNING OF GOVERNMENT IN NIGERIAN SENIOR SECONDARY SCHOOLS - Lysias Dodd Gilbert (European Scientific Journal, ESJ, 2014)
Cognizant of Nigeria's quest for the consolidation of her nascent democratic experience, the teaching and learning of Government as an academic discipline is of great importance to the contemporary Nigerian society. The significance clearly transcends but includes, the inculcation of the spirit of patriotism and nationalism in Nigerian students (future leaders), exposing them to the dynamics of the Nigerian political system, engaging students in rigorous intellectual training and development, training of students in the art of constructive, sequential and objective analysis and presentation of facts with near scientific prediction and conclusion. In addition, are the facts that Government trains students in character development, exposes them to the dynamics of international relations and instills in them the much needed civic attitudes required for a free, democratic, just and egalitarian state. However, despite the importance of teaching and learning of the subject, there are numerous factors militating against it in Nigerian Senior Secondary Schools. Against this backdrop, this paper reviews the factors militating against the effective teaching and learning of Government in Nigerian Senior Secondary Schools and concludes that the most critical of these problems are the non-availability of professionally trained teachers and relevant instructional materials peculiar to the subject.